2007
DOI: 10.1057/palgrave.jit.2000095
|View full text |Cite
|
Sign up to set email alerts
|

Management of Trust in the E-Marketplace: The Role of the Buyer's Experience in Building Trust

Abstract: The e-marketplace, or broker-managed online market, is one of today's most profitable e-business models. In these marketplaces, buyers routinely engage with businesses and individual sellers with whom they have had little or no prior interaction, making trust one of the most important issues in the e-marketplaces. Therefore, a clear understanding of the trust building process in the e-marketplace is important for the success in the market. In this study, we analyze the process by which e-marketplace customers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 49 publications
9
68
3
2
Order By: Relevance
“…Academic research on website quality has also identified content and customer service as important dimensions in defining a service quality scale for online retailers (Wolfinbarger and Gilly, 2003). Similar results were confirmed by Kim and Ahn (2007) in their empirical study of electronic marketplaces.…”
Section: Content Management and Customer Service Management Systemssupporting
confidence: 52%
“…Academic research on website quality has also identified content and customer service as important dimensions in defining a service quality scale for online retailers (Wolfinbarger and Gilly, 2003). Similar results were confirmed by Kim and Ahn (2007) in their empirical study of electronic marketplaces.…”
Section: Content Management and Customer Service Management Systemssupporting
confidence: 52%
“…The key distinction between emarketplaces and online storefronts lies in the role of the merchant, that is, e-marketplaces act as an intermediary between sellers and buyers, whereas storefronts (or e-tailers) are responsible for selling to consumers (Hong & Cho, 2011). Previous studies found that e-marketplaces tend to be riskier than e-tailers (Kim & Ahn, 2007). E-marketplaces have limited control over sales transactions in which sellers fulfill online orders.…”
Section: H3mentioning
confidence: 99%
“…Although online consumers are generally concerned about the legitimacy of vendors, and the authenticity of products or services, buyers using e-marketplaces are more likely to be exposed to the risks associated with the opportunistic behavior of sellers, than those using online storefronts (Pavlou & Gefen, 2004). In addition, in an e-marketplace, buyers routinely engage in transactions with unfamiliar businesses and individual sellers (Kim & Ahn, 2007). For this reason, e-marketplaces are typically considered riskier than e-tailers.…”
Section: (4) Situational Involvement and Trust Expectationmentioning
confidence: 99%
“…Specifically, we assumed that there were only two key attributes (i.e., transaction probability and listing fee). In reality, auction websites could differ in some other features, such as eBay's Feedback Forum to promote trust (Kim and Ahn 2007;Ba and Pavlou 2002). Moreover, other market level factors, such as product supply and the cost of holding on to the products by the sellers, could affect the results.…”
Section: Discussionmentioning
confidence: 99%